Ling-gui-zhu-gan granules reduces obesity and ameliorates metabolic disorders by inducing white adipose tissue browning in obese mice - Li, Yuxiu; Ye, Zimengwei; Zhao, Yi; Xu, Bingrui; Xue, Wanying; Wang, Zhufeng; An, Ran; Wang, Fan; Wu, Rui (Frontiers in Physiology, 2024)
Background: Ling-gui-zhu-gan (LGZG) formula has been demonstrated to effectively ameliorate the clinical symptoms of patients with obesity or metabolic syndrome. This study aimed to explore both the effect and the underlying mechanisms of LGZG against obesity. Methods: Male C57BL/6N mice were randomized into four groups (n = 8): normal control (NC), obese (OB), metformin (Met), and LGZG. After 8 weeks of gavage administration, the pharmacological effects of LGZG on obesity and metabolism were investigated using biochemical parameters, histomorphological examination, and lipidomics techniques. Pivotal factors associated with white adipose tissue browning were evaluated using quantitative real-time polymerase chain reaction and western blotting. Results: The results revealed that LGZG reduced the levels of obesity markers, including body weights, body fat mass and food intake in obese mice. Further evaluations highlighted that LGZG restored glucose homeostasis and significantly improved insulin sensitivity in obese mice. Importantly, LGZG could adjust serum lipid profiles and regulate the lipidomic spectrum of intestinal contents, with noticeable shifts in the levels of certain lipids, particularly diacylglycerols and monoacylglycerols. Histopathological examinations of LGZG-treated mice also revealed more favorable adipose tissue structures than their obese counterparts. Furthermore, we found that LGZG upregulated the expression of several key thermogenesis-related factors, such as UCP1, PRDM16, PGC-1α, PPARα, PPARγ, CTBP1, and CTBP2 in white adipose tissues. Conclusion: Our findings position LGZG as a novel strategy for preventing obesity and improving metabolic health. Keywords: Chinese herbal formula, obesity, glucolipid metabolism disorder, adipose browning effect, thermogenesis, UCP1